Peningkatan Kesejahteraan UKM Mulyo Waras melalui Pelatihan Pembuatan Pakan Domba dengan Mesin Pencacah Semi-Otomatis: Improving The Welfare Of UKM Mulyo Waras By Training In Making Sheep Feed Using A Semi-Automatic Chopper Machine - Karminto, Karminto; Priyanto, Kaleb; Heru Palmiyanto, Martinus; Hari Priyambodo, Bambang; Suhartoyo, Suhartoyo; Tritmoko, Nugroho (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
Wonogiri Regency, Central Java, is famous for its large number of residents who work as breeders, especially sheep/goat breeders. The feed for goats/sheep breeders in Wonogiri district is sourced from weeds. However, the enumeration was still done manually using a sickle, so the enumeration process was ineffective because it required more time and effort. Through this community service scheme, the process of making a machine for chopping weeds is carried out which will later be used as fodder for goats/sheep, especially in the Wonogiri area. The machine is driven by an electric motor and there is a chopping knife which is designed to be more effective. The results of this community service program show that the increase in sheep feed production increased from 200 kg/day before using the machine to 350 kg/day or an increase of up to 75% when compared to without the chopping machine.